Match Performance Comparison in Top English Soccer Leagues - Di Salvo, V.; Pigozzi, F.; González-Haro, C.; Laughlin, M. S.; De Witt, J. K. (International Journal of Sports Medicine, 2013)
The purpose of this study was to compare motions of soccer players in the English Premier (1st) and Championship (2nd) League. A total of 26 449 observations were obtained from players during 4 seasons (2006–2010) in the 2 leagues. Time-motions of all players (attackers, central defenders, central midfielders, wide defenders, wide midfielders) were recorded during each match using the Prozone® System, (Leeds, UK), and categorized by speed intensity. Number of actions, total distance and the mean distance covered at each speed intensity were measured. Players in the Championship league covered a total match distance of 11.1±0.9 km compared with 10.8±1.0 km for players from the Premiership (p<0.001). Championship players also covered greater distances during jogging, running, high-speed running, and sprinting. Premiership players covered more distance walking. Players in the Soccer League Championship had more instances of each condition. Although these differences were statistically significant, they were negligible in practical terms, suggesting match-related activities do not explain the general superiority of Premiership players over Championship players in England.
Keywords: soccer; leagues comparison; player position; match analysis; physical performance; specific training